ANALISIS KINERJA PERUSAHAAN DENGAN BALANCED SCORECARD (Studi Kasus Pada ID Express Soloraya) - Aisyah Desnilia; Rukmini Rukmini; LMS Kristiyanti (Jurnal Akuntansi dan Pajak, 2022)
This research was conducted with the aim of knowing the simultaneous and partial effect of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective on the performance of ID Express delivery service companies. The research was conducted using a quantitative descriptive approach, with a sample of 33 respondents. The data analys metode used multiple linear regression analysis. The results of research conducted simultaneously on the financial perspective, customer perspective, internal business process perspective and learning and growth perspective obtained Fcount value of 20.541 > Ftable 2.714 with a probability of 0.000 (p value